Effect of temperature and air velocity on drying kinetics, antioxidant capacity, total phenolic content, colour, texture and microstructure of apple (var. Granny Smith) slices - Vega Gálvez, Antonio (2012)
The aim of this work was to study the effect of temperature and air velocity on the drying kinetics and quality attributes of apple (var. Granny Smith) slices during drying. Experiments were conducted at 40, 60 and 80 °C, as well as at air velocities of 0.5, 1.0 and 1.5 m s -1.Effective moisture diffusivity increased with temperature and air velocity, reaching a value of 5.30x10-9 m2 s-1 at maximum temperature and air velocity under study. The rehydration ratio changed with varying both air velocity and temperature indicating tissue damage due to processing. The colour difference, ∆E, showed the best results at 80 °C. The DPPH-radical scavenging activity at 40 °C and 0.5 m s -1 showed the highest antioxidant activity, closest to that of the fresh sample. Although ∆E decreased with temperature, antioxidant activity barely varied and even increased at high air velocities, revealing an antioxidant capacity of the browning products. The total phenolics decreased with temperature, but at high air velocity retardation of thermal degradation was observed. Firmness was also determined and explained using glass Transition concept and microstructure analysis.